Resale Price Maintenance and the Private Antitrust Plaintiff - Roger D. Blair; John E. Lopatka; Jill Boylston Herndon (Washington University Law Quarterly, 2005)
How does the law reconcile the per se illegality of an economically ambiguous practice with enforcement doctrines that permit only those directly suffering anticompetitive harm to sue and require them to prove damages coherently? The question is critical in resale price maintenance (“RPM”) cases because the practice, though illegal per se, may produce no anticompetitive harm, injure parties more proximate to the violation than the plaintiffs, or cause damages resistant to reasonable estimation. One purpose of this Article is to apply economic theory to identify antitrust injuries caused by RPM in various settings. In addition, antitrust law has long required plaintiffs to estimate reasonably if not precisely the magnitude of the harm they suffered as a result of the violation, and we apply this mandate to claims of injury caused by RPM. We demonstrate that plaintiffs will often be hard-pressed—if not unable—to prove damages in an economically coherent fashion. We also explore the implications of the prohibition against indirect purchaser suits in the context of RPM. In all, the Article provides a comprehensive examination of the major issues involved in private actions to obtain damages for illegal RPM agreements. We begin in the next Part with an overview of the legal requirements for plaintiffs to establish antitrust injury and antitrust standing. We briefly survey the history of RPM law in Part III, demonstrating that the Court’s failure to provide a coherent economic case for per se condemnation creates nearly insurmountable problems for private plaintiffs in proving antitrust injury and damages. We illustrate these problems in Part IV through an examination of various business motivations for using RPM—some with anticompetitive effects, some with procompetitive effects, and some with confounding effects. Sorting out the competitive effects of a particular RPM plan is no mean feat. Consequently, the private plaintiff faces a substantial, if not insurmountable, barrier in proving antitrust injury and damages. Because of the formidable impediments faced by private antitrust plaintiffs, one might expect that a defendant would be reluctant to pay anything to settle a private RPM action. But a large number of RPM cases do settle, and Part V addresses the possible reasons for this surprising outcome. We offer some final thoughts in Part VI.
Keywords: Price maintenance; Compensatory damages – Economic aspects; Burden of proof; Indirect purchaser doctrine (Antitrust law); Antitrust law; United States